Geographic disparities in access to Medication for Opioid Use Disorder across US census tracts based on treatment utilization behavior. (June 2022) - Mitchell, Penelope; Samsel, Steven; Curtin, Kevin M.; Price, Ashleigh; Turner, Daniel; Tramp, Ryan; Hudnall, Matthew; Parton, Jason; Lewis, Dwight
Abstract: Drug overdose is the leading cause of accidental death in the U.S. with deaths from opioid overdose occurring at a higher rate in rural areas. The gaps in the provision of healthcare services have been exacerbated by the opioid crisis leaving vulnerable populations without access to preventative care and education, harm reduction, both chronic and acute treatment of the symptoms of opioid use disorder (OUD), and long-term psychological support for those with OUD and their families. There has been a call in the literature -and a federal mandate-for increased access to opioid treatment facilities, but to date this access has not been operationalized using best practices in geography. Medication for Opioid Use Disorder (MOUD) with FDA-approved methadone or buprenorphine has been shown to increase treatment retention, reduce opioid use and associated health and societal harms, and reduce opioid related overdose, and as such is considered the most effective treatment for OUD. The objective of this study is to examine U.S. adults' spatial access to MOUD — specifically locations of certified Opioid Treatment Programs (OTPs) and DATA-waived Buprenorphine providers. A gravity-based variant of the enhanced two-step floating catchment area model is employed, where friction of distance is based on previously published willingness to travel distances for patients visiting OTPs, to assess how opioid agonist treatment accessibility varies across the nation. Findings suggest that there are extensive 'treatment deserts' where there is little to no physical access to MOUD, especially in rural areas. The significance of this work lies in the incorporation of treatment utilization behavior in the access metric, and the continued confirmation of gaps in access to OUD services despite federal efforts to improve accessibility. Highlights: Quantified spatial access to MOUD is needed to identify shortage areas. Utilization-based distance decay in E2SFCA depicts realistic MOUD spatial access. Disparities in access to MOUD impact rural tracts more acutely. Clusters of low to no MOUD access more than double from urban to large rural tracts.